E-health in Latin America and the Caribbean : progress and challenges - Fernandez, Andres (United Nations New YorkUS, 2011)
Reports on the issues coming out from the workshop on Regional e-Health and Telemedicine Goals and Policy Follow-up hosted in part by ECLAC in 2009. Looks at the promise that e-Health holds fro meeting health-care challenges through expanding access to quality health care; examines the progress and challenges in the area of e-Health and telemedicine in 12 Latin American countries and 8 countries from the Caribbean subregion.